Quality Improvement Project to Improve the Timeliness of Care for Children With Testicular Torsion in the Emergency Department. Issue 4 (18th July 2022) - Chinta, Sri S.; Gray, Matthew P.; Kopetsky, Matthew; Baumer-Mouradian, Shannon H.; Drendel, Amy L.; Roth, Elizabeth; Ferguson, Catherine C.; Nimmer, Mark; Boyd, Kevin; Brousseau, David C.
Abstract : Introduction: Testicular torsion (TT) is a urologic emergency that requires timely diagnosis and surgery. We noted variation in the door-to-detorsion times for patients with TT at our institution and our orchiectomy rate was 25.8%. We aimed to decrease the mean door-to-detorsion time from 124.6 to 114.6 minutes or less over 12 months. Methods: A multidisciplinary team of pediatric emergency medicine, radiology, urology physicians, and nurses, was formed. Our key drivers were use of Testicular Workup for Ischemia and Suspected Torsion (TWIST) score, prompt urology consultation, and efficient transfer from emergency department (ED) to operating room. Our process measures were TWIST score documentation rate and early urology consultation rate, outcome measures were door-to-detorsion time and orchiectomy rate, and balancing measure was ultrasound utilization rate. Early urology consultation occurred when the ED provider documented telephone communication with urology, immediately after placing a testicular doppler ultrasound (TDUS) order and before TDUS result. Results: Over 2 years, 45 cases of TT were diagnosed. TWIST score documentation was implemented and was sustained at 78%. This improved early urology consultations from 40% to 60%. The mean door-to-detorsion time improved from 124.6 to 114.2 minutes. There was no reduction in the orchiectomy rate or TDUS utilization rate. Conclusions: A quality improvement project to improve the timeliness of care for children with TT resulted in expedited ED care but did not impact the orchiectomy rate.